Identification of peculiarities of reactive anxiety experienced by professionals of socioeducational activities, employing quantitative and qualitative methods - Alifanovienė, Daiva; Vaitkevičienė, Asta; Lučinskaitė, Laura (Social Welfare: Interdisciplinary Approach, 2012)
The article deals with peculiarities of the reactive anxiety state of professionals of socioeducational activities (social pedagogues and social workers). Spielberger’s and Chanin’s personal anxiety scale, illustrating anxiety peculiarities experienced by these professionals, is given. Evaluating peculiarities of these professionals’ reactive anxiety, methods of descriptive mathematical statistics, multidimentional statistics (factor analysis) were used, the method of qualitative research semi-structured interview, content analysis were also applied. It was found that the majority of socioeducational activity professionals experienced mild reactive anxiety, about one third of respondents felt moderate reactive anxiety and a small part, severe reactive anxiety. Such state of respondents enables to avoid big anxiety and psychosomatic disorders.
Keywords: anxiety; state of anxiety; reactive anxiety; professionals of socioeducational activities